การพัฒนารูปแบบการประเมินองค์การแบบสมดุลสำหรับโรงเรียนคาทอลิก สังกัดอัครสังฆมณฑลกรุงเทพมหานคร - วีณา อ่องแสงคุณ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purpose of this research is to develop the Balanced Scorecard Model for Catholic Schools under Bangkok Archdiocese. The findings are : 1. The Balanced Scorecard Model consists of 4 perspectives 1) The Student Perspective comprising 5 strategic objectives : the students high moral and ethical standards with good characteristics, the students capability to create their own knowledge, the students learning achievement , the students competencies and skill in foreign languages and the students competencies and skill in information and communication technology 2) The Internal Process Perspective comprising 4 strategic Objectives; Good Governance under School-Based Management, Strategic Management, The school s curriculum based on Catholic Educational Philosophy and educational standard assurance system 3) The Learning and Growth Perspective comprising 3 strategic objectives; the teachers and staffs capability and competencies, Knowledge Management System and information and communication technolgoy in school administration 4) The Budget and Resources Perspective comprising 3 strategic objectives; Performance-Based Budgeting System, The effectiveness of school resources allocation and school net work and alliances. 2. The components and contents developed from the model are a vision, missions, goals and strategies of the Catholic school including 15 strategic objectives in 4 perspectives, a strategy map, 40 key performance indicators, the KPT Templates. Strategic initiatives, 9 sets of instruments for KPI evaluation and the performance evaluation form covering the school s performance in each perspective and in a whole school. 3. The experts agreed that the Balanced Scorecard Model developed from this study was suitable and probable at high and highest level with [mean] = 4.15 - 4.76 and [mean] = 4.00 - 4.69